2020
DOI: 10.1126/sciadv.abc5801
|View full text |Cite
|
Sign up to set email alerts
|

Non-neuronal expression of SARS-CoV-2 entry genes in the olfactory system suggests mechanisms underlying COVID-19-associated anosmia

Abstract: Abstract:Altered olfactory function is a common symptom of COVID-19, but its etiology is unknown. A key question is whether SARS-CoV-2 (CoV-2) – the causal agent in COVID-19 – affects olfaction directly, by infecting olfactory sensory neurons or their targets in the olfactory bulb, or indirectly, through perturbation of supporting cells. Here we identify cell types in the olfactory epithelium and olfactory bulb that express SARS-CoV-2 cell entry molecules. Bulk sequencing demonstrated that mouse, non-human pri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
784
4
49

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,012 publications
(955 citation statements)
references
References 131 publications
34
784
4
49
Order By: Relevance
“…3D), possibly due to loss of cell markers during SARS-CoV-2 infection, as has also been observed with influenza infection [36]. Similar to what others have observed [11, 12, 37], we found low level expression of ACE2 in our primary human epithelial cells (Fig. 3A-E), likely reflecting the limited sensitivity of scRNA sequencing.…”
Section: Resultssupporting
confidence: 88%
“…3D), possibly due to loss of cell markers during SARS-CoV-2 infection, as has also been observed with influenza infection [36]. Similar to what others have observed [11, 12, 37], we found low level expression of ACE2 in our primary human epithelial cells (Fig. 3A-E), likely reflecting the limited sensitivity of scRNA sequencing.…”
Section: Resultssupporting
confidence: 88%
“…The anatomy of the olfactory recess and the relationship among the nasal epithelium, OB, and CNS allows for a natural pathway for virus spread via neuronal transport. 25 Trans-synaptic transfer of virus is described in SARS-CoV 26 and Middle East respiratory syndrome coronavirus, 27 betacoronaviruses homologous to SARS-CoV-2 and responsible for previous epidemics. Preclinical experiments in transgenic mice demonstrated that the intranasal introduction of these viruses resulted in CNS inoculation, with neuronal loss in areas of viral expression.…”
Section: Discussionmentioning
confidence: 99%
“…Findings remain significant even with the exclusion of the COVID-19 high outlier depicted at a mean normalized OB T2 FLAIR signal intensity of 3.1. in sustentacular and olfactory stem cells and may serve as a putative target for SARS-CoV-2 infection of olfactory epithelium. 25 Alternatively, viral binding to angiotensin-converting enzyme 2 receptors expressed in CNS capillary endothelium might result in endothelial damage, which enables spike protein binding to neuronal angiotensin-converting enzyme 2 receptors and subsequent CNS infection. 28 Another possibility is that hematogenous spread may occur via the blood supply shared by olfactory sensory neurons and the OB.…”
Section: Discussionmentioning
confidence: 99%
“…As far as SARS-CoV and MERS-CoV are concerned, experimental studies of animal models showed that SARS-CoV and MERS-CoV, when given through the nose, possibly invade the cerebrum via the olfactory nerves, spreading to some regions of the brain including thalamus and brainstem (8,20,34). Notably, it has been suggested that ACE2 olfactory (epithelial) support cells and stem cells produce ACE2 genes, as do cells located in the epithelium of the nasal respiratory tract in patients afflicted with COVID-19, which may show some parallels with attentiondeficit/hyperactivity disorder (39)(40)(41). So far, in the light of the evidence provided enough, it is conceivable that SARS-CoV-2 is neuroinvasive, and it uses ACE2 as receptors to penetrate the cell (13).…”
Section: Neuroinvasion Of Sars-cov-2 and Samhd1mentioning
confidence: 99%